Understanding the differences in the use of graphic tool and planning during graphic execution between individuals with autism and typically developing individuals - Verma, Pragya; Singh, Madhu; Lahiri, Uttama (Frontiers in Education, 2024)
Individuals with Autism (ASD) often face difficulty in executing graphic tasks. This can be related to how one uses a graphic tool (e.g., pen) and plans ahead the graphic execution. Use of graphic tool can be captured using attributes, e.g., pen-tip pressure, number of pen lifts, etc. One’s ability to plan a graphic execution can be quantified using the total duration of pen lifts (i.e., air time). Though pen-and-paper-based Trail Making Test-Part A (TMT-A) can estimate planning of graphic execution, yet it cannot capture other attributes, e.g., pen-tip pressure, pen lift, etc. This can be possible if TMT-A is administered on a pressure-sensitive tablet as seen from existing studies with Typically Developing (TD) individuals. However, quantification of such attributes using TMT-A administered on a pressure-sensitive tablet remains unexplored for individuals with ASD. In addition, such objective measures can help to understand variations in the use of graphic tool and ability to plan graphic execution even outside the TMT-A task, e.g., while drawing shapes which is important to the development of children’s graphic skills. Here, we conducted a study with 12 pairs of TD children and those with ASD who executed TMT-A (in Phase-I) and Shape drawing (in Phase-II) on a pressure-sensitive tablet. Results of our study show differences in the use of graphic tool and planning ahead the graphic execution between two participant groups in both the Phases. Such insights can offer clinical inputs that can be helpful in designing individualized intervention paradigms for children facing difficulties in graphic execution.